World Trends in Infant Formulas Composition Enhancement - Irina A. Belyaeva; Leyla S. Namazova-Baranova; Elena P. Bombardirova; Tatiana V. Turti (Вопросы современной педиатрии, 2023)
This article provides the overview of the major strategies for infant formulas composition enhancement via modern technologies and trends in minimizing technology-related loads on the environment. Potential modifications of quantitative and qualitative characteristics of milk formulas nutrients have been determined. We also covered product contents changing over age, as well as the perspectives of using animal milk in formulas. The relevance of adding biologically active substances and living microorganisms (probiotics), their safety, and efficacy are discussed.